Research on the propagation mechanism of hydraulic fractures in infill horizontal wells - Liu, Erhu; Yao, Tingwei; Qiao, Lianlian; Li, Jing; Wang, Haiyang; Gao, Qian (Frontiers in Earth Science, 2022)
In recent years, infill horizontal well technology has been used to develop oil and gas in the remaining oil areas of unconventional low-permeability reservoirs. However, the initial fractures in parent wells will affect the hydraulic fractures formed by fracturing infilling horizontal wells. The interaction mechanisms between initial fractures and artificial fractures in infill horizontal wells are still unclear. Combined with the boundary element method and the maximum circumferential tensile stress criterion, a numerical model of hydraulic fracturing that can simulate the evolution of fracture trajectory and stress field was established. The analytical solution of the hydraulic fracture-induced stress field was used to verify the accuracy of the model. Using this model, propagation of hydraulic fractures in infill horizontal wells under different conditions was analyzed. Simulation results show that both the fracture spacing and well spacing have a significant impact on the propagation trajectory of hydraulic fractures in infill horizontal wells. The shorter the fracture spacing and well spacing is, the stronger the inter-fracture stress interference between the initial fractures and hydraulic fractures is. Reasonable fracture spacing and well spacing can enhance the induced stress field and form a complex fracture network in the reservoir. Too small well spacing may cause artificial fractures to communicate with initial fractures, thereby reducing hydraulic fracturing efficiency and limiting the stimulation volume of the reservoir.